Population geography II: The r/age of migration - Darren Smith (2018)
This second report focuses on the social impacts of migration in the context of the increasing politicization and contestation of migration. It is argued that Population Geography could engage in more effective ways with political debates of migration. A call is made for Population Geography to more readily provide robust evidence to shape debates, such as Brexit, and to inform the salience of ‘raging comments’ based on representations of migration as a harbinger of detrimental changes to local neighbourhoods. The discussion outlines scholarship from the UK and USA that progresses knowledge of changing population compositions and migration, to illustrate some ways that Population Geography can make valuable interventions within political, policy, media and lay discourses of migration. The paper concludes by highlighting some questions for Population Geography to reflect upon as a starting point for a more impactful Population Geography.